Infant-Associated Bifidobacterial β-Galactosidases and Their Ability to Synthesize Galacto-Oligosaccharides - Ambrogi, Valentina; Bottacini, Francesca; O’Callaghan, John; Casey, Eoghan; van Breen, Justin; Schoemaker, Barry; Cao, Linqiu; Kuipers, Bas; O’Connell Motherway, Mary; Schoterman, Margriet; van Sinderen, Douwe (Frontiers in Microbiology, 2021)
Galacto-oligosaccharides (GOS) represent non-digestible glycans that are commercially produced by transgalactosylation of lactose, and that are widely used as functional food ingredients in prebiotic formulations, in particular in infant nutrition. GOS consumption has been reported to enhance growth of specific bacteria in the gut, in particular bifidobacteria, thereby supporting a balanced gut microbiota. In a previous study, we assessed the hydrolytic activity and substrate specificity of seventeen predicted β-galactosidases encoded by various species and strains of infant-associated bifidobacteria. In the current study, we further characterized seven out of these seventeen bifidobacterial β-galactosidases in terms of their kinetics, enzyme stability and oligomeric state. Accordingly, we established whether these β-galactosidases are capable of synthesizing GOS via enzymatic transgalactosylation employing lactose as the feed substrate. Our findings show that the seven selected enzymes all possess such transgalactosylation activity, though they appear to differ in their efficiency by which they perform this reaction. From chromatography analysis, it seems that these enzymes generate two distinct GOS mixtures: GOS with a relatively short or long degree of polymerization profile. These findings may be the stepping stone for further studies aimed at synthesizing new GOS variants with novel and/or enhanced prebiotic activities and potential for industrial applications.